Pelatihan Kepemimpinan Bagi Para Leader PP. Bayt Al-Hikmah Kota Pasuruan - Fitri Kurnia; Nailatul Khoiriyah; Ahmad Aris Fajarudin (STIT Al - Ibrohimy Bangkalan, 2025)
Leadership is a fundamental aspect of pesantren organizational management, particularly in facing the challenges of the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity). These conditions require leaders who are adaptive, visionary, and capable of integrating Islamic values with modern managerial competencies. A leadership training program conducted at PP. Bayt Al-Hikmah Pasuruan was designed to enhance leaders’ capacities through participatory and applicative approaches. The two-day program employed interactive lectures, team-building activities, group discussions, role-play simulations, and question-and-answer sessions. The results revealed a significant improvement in participants’ understanding of visionary leadership, communication skills, decision-making abilities, and adaptability to organizational changes. Beyond the individual impact, the program also strengthened pesantren governance, encouraged collaborative leadership practices, and fostered synergy between higher education institutions and the community. Thus, this training contributes not only to developing pesantren leaders’ competencies but also serves as a model of Tri Dharma Perguruan Tinggi implementation that can be replicated in similar institutions.